A prospective multicenter evaluation of direct molecular detection of blood stream infection from a clinical perspective. Issue 1 (December 2016) - Nieman, A.; Savelkoul, P.; Beishuizen, A.; Henrich, B.; Lamik, B.; MacKenzie, C.; Kindgen-Milles, D.; Helmers, A.; Diaz, C.; Sakka, S.; Schade, R.
Abstract Background Rapid diagnosis and appropriate antimicrobial therapy are of major importance to decrease morbidity and mortality in patients with blood stream infections (BSI). Blood culture, the current gold standard for detecting bacteria in blood, requires at least 24–48 hours and has limited sensitivity if obtained during antibiotic treatment of the patient. The aim of this prospective multicenter study was to clinically evaluate the application of a commercial universal 16S/18S rDNA PCR, SepsiTest™ (PCR-ST), directly on whole blood. Methods In total 236 samples from 166 patients with suspected sepsis were included in the study. PCR-ST results were compared to blood culture, the current gold standard for detecting BSI. Because blood cultures can give false-negative results, we performed an additional analysis to interpret the likelihood of bloodstream infection by using an evaluation based on clinical diagnosis, other diagnostic tests and laboratory parameters. Results Clinical interpretation of results defined the detected organism to be contaminants in 22 of 43 positive blood cultures (51.2 %) and 21 of 47 positive PCR-ST results (44.7 %). Excluding these contaminants resulted in an overall sensitivity and specificity of the PCR-ST of 66.7 and 94.4 % respectively. Of the 36 clinically relevant samples, 11 BSI were detected with both techniques, 15 BSI were detected with PCR-ST only and 10 with blood culture only. Therefore, in this study, SepsiTest™ detected an additional 71 % BSI compared to blood culture alone. Conclusions More clinically relevant BSI were diagnosed by molecular detection, which might influence patient treatment. An improved SepsiTest™ assay suited for routine use can have additional value to blood culture in diagnosing bacteremia in septic patients.